The Languages without Borders Program as a teacher education policy in Brazil - Welp, Anamaria Kurtz de Souza; Didio, Álvaro Rutkoski (Olhares & Trilhas, 2019)
This article aims to present part of an investigation conducted in the Language Center of the Languages Without Borders Program (LwB) of an important public university in the south of Brazil. The research had the objective of analyzing the narratives produced by three English teachers linked to the LwB, starting from the following question: What factors most contributed to your professional development within the LwB context? For the generation of the data, semi-structured interviews were conducted through which the three teachers were encouraged to produce narratives about their education in the LwB context. The results of the analysis of the teachers‘ accounts suggest that pre-service teachers should prepare themselves for self-reflection and self-analysis, as it is impracticable to separate personal and professional dimensions. The narratives also point to the importance programs such as LwB, which put pre-service teachers in the classroom during their undergraduate years so that their professional development is based on concrete case discussions that aim at articulating theory and practice.KEYWORDS: Teacher education; Internationalization; Languages without Borders